Stem cell−enriched hybrid breast reconstruction reduces risk for capsular contracture in a hybrid breast model - Diehm, Yannick; Thomé, Julia Maria; Will-Marks, Patrick; Kotsougiani-Fischer, Dimitra; Haug, Valentin; Siegwart, Laura; Kneser, Ulrich; Fischer, Sebastian (Plastic and reconstructive surgery, 2023)
Background: - Hybrid breast reconstruction (HBR) combines silicone implants with fat grafting to improve implant coverage, treating local tissue deficiencies and leading to a more natural breast appearance. Recent data also indicated less capsular contracture after HBR. The authors developed a novel technique and animal model of cell-assisted (CA) HBR to illuminate its effects on capsular contracture. - Methods: - Animals received silicone implants in a dorsal submuscular pocket. Although animals of the HBR group received fat grafting around the implant without stem cell enrichment, rats of the CA-HBR1 and the CA-HBR2 groups received stem cell-enriched fat grafting with 2 × 106 and 4 × 106 adipose-derived stem cells immediately after implant insertion. On day 60, animals underwent sonography and elastography imaging and were euthanized, and outcome analysis was performed by means of histology, immunohistochemistry, chemical collagen quantification, and gene expression analysis. - Results: - With this novel technique, long-term survival of adipose-derived stem cells within the implant pocket was demonstrated after 60 days after implant insertion. CA-HBR led to significantly reduced thickness and collagen density of capsular contractures. In addition, CA-HBR resulted in reduced fibrotic responses with less occurrence of collagen type I and transforming growth factor-β in capsule tissue. Moreover, the addition of stem cells suppressed fibrotic and inflammatory responses on a genetic level with significant underexpression of collagen type I and transforming growth factor-β1. - Conclusions: - With this new technique and animal model, the authors observed a preventive effect on capsular contracture substantiating the basis of clinical outcomes of HBR. The authors propose that the addition of stem cells to HBR might booster its beneficial results. - Clinical Relevance Statement: - Stem cell-enriched fat grafting around silicone implants may reduce the risk for capsular contracture after silicone breast implantation. While fat grafting alone already shows beneficial effects, the addition of stem cells to the fat graft can potentiate this effect.
Gesehen am 23.10.2023